Liberated or Recolonized: Making the Case for Embodied Evaluation in Peacebuilding - Ruby Quantson Davis (The Evaluation Center at Western Michigan University, 2023)
The quest to liberate and decolonize evaluation could create a recolonizing process in development evaluation unless practitioners pay attention to an embodied process that allows persons and communities in the global south to bring all of their epistemologies to an evaluation process. This will enable evaluation to be a learning process through which communities gain insights from their programs through their own ways of knowing. Constrained by time, resources, and limited commitment to the decolonization agenda, organizations and experts in evaluation could cause further harm to indigenous and local ways of knowing through half-baked decolonization processes . Through the lens of peacebuilding, this paper proposes an embodied evaluation as a practical way to decolonize evaluation, and reduce the risk of recolonizing the concepts and processes of project evaluation while addressing some of the power imbalances that lie beneath traditional evaluation and development. This paper suggests that monitoring , evaluation and learning of projects should be led by those most affected and closest to the problem being addressed and experts who assist in these processes should a assume a collaborative approach that requires the embodiment of the process and experiences of the affected. This approach is likely to generate reports through the world views of those affected and reduce dominance and imposition of external methodologies that distort outcomes of programmes. This paper is a reflection on practice, and a prompt for further research on embodied evaluation as a decolonizing agenda.